2020
DOI: 10.1101/2020.02.10.941328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic predictors of participation in optional components of UK Biobank

Abstract: Large studies (e.g. UK Biobank) are increasingly used for GWAS and Mendelian randomization (MR) studies. Selection into and dropout from studies may bias genetic and phenotypic associations. We examine genetic factors affecting participation in four optional components in up to 451,306 UK Biobank participants.We used GWAS to identify genetic variants associated with participation, MR to estimate effects of phenotypes on participation, and genetic correlations to compare participation bias across different stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Similarly, a complete case analysis will generally produce unbiased estimates of the exposure-outcome association if missingness is unrelated to the outcome of interest [24]. We found that many baseline and later measures were associated with ongoing participation; this finding is unlikely to be unique to ALSPAC, as indicated recently [25]. This suggests that -firstly -a wide range of baseline covariates may need to be included in the (complete case) analysisor imputation/weighting model -in order for the assumptions to be met.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, a complete case analysis will generally produce unbiased estimates of the exposure-outcome association if missingness is unrelated to the outcome of interest [24]. We found that many baseline and later measures were associated with ongoing participation; this finding is unlikely to be unique to ALSPAC, as indicated recently [25]. This suggests that -firstly -a wide range of baseline covariates may need to be included in the (complete case) analysisor imputation/weighting model -in order for the assumptions to be met.…”
Section: Discussionsupporting
confidence: 66%
“…Medical and scientific interest: Studies recruiting voluntary samples may be biased as they are likely to contain a disproportionate amount of people who have a strong medical or scientific interest. It is likely that these people will themselves have greater health awareness, healthier behaviour, be more educated, and have higher incomes 31,52 .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of psychiatric disorders in UK Biobank is complicated by both recruitment bias away from more severe psychiatric disorders and incomplete data on participants 10,[33][34][35] . The most comprehensive data are available on a subset of UK Biobank individuals from a mental health questionnaire for which participants were invited by email (n = 157,366) 34 .…”
Section: Figure 3 Effect Of S Het Burden On Traits Known To Be Assocmentioning
confidence: 99%
“…When possible, we used independent estimates from population level or external data to alleviate biases in UK Biobank phenotype ascertainment ( Supplementary Figure 18) 35 . As such, data on cognitive ability and fertility are collected from Swedish population-level government administrative registers that have been linked to Swedish conscription registers 65 .…”
Section: General Cognitionmentioning
confidence: 99%